Airplanes - Parker, Steve; Wilks, Peter (Brookfield, Conn. : Copper Beech Books, 1995)
An imaginative look at airplanes through such questions as "What if airplanes didn't have air?" and "What if airplanes could go into space?"
Includes index.
Keywords: Airplanes -- Juvenile literature; Airplanes -- Miscellanea; Questions and answers